Adjustable electronic and optical properties of BlueP/MoS2 van der Waals heterostructure by external strain: a first-principles study. (30th June 2020) - Yang, Fei; Han, Junnan; Zhang, Le; Tang, Xianhong; Zhuo, Zhenguo; Tao, Yue; Cao, Xincheng; Dai, Yuehua
Abstract: Blue phosphorene (BlueP) has been widely researched recently as a potential material for novel photocatalytic and electronic devices. In this letter, due to its similar in-plane hexagonal lattice structure to MoS2, BlueP/MoS2 van der Waals heterostructures were built in six configurations. The II-stacking configuration was the most stable due to the lowest binding energy obtained from the calculation results. Furthermore, by controlling the external vertical strain, the geometry structures were optimized and the electronic structures of the BlueP/MoS2 heterostructure were modulated. We found that when the interlayer distance was 3.71 Å, the structure was the most optimized. In addition, as the result of charge transfer at the interlayer, a built-in electric field was formed in the BlueP/MoS2 heterostructure, which explained the formation of the type-II band alignment structure. The optical properties results show that the BlueP/MoS2 heterostructure has a wide optical response range and good light absorption ability, which indicated significant potential for BlueP/MoS2 heterostructure use in the next generation of photovoltaic devices and water-splitting materials.